Potensi Efektivitas Pemanfaatan Penargetan Lokasi Google Ads sebagai Strategi Promosi Digital untuk Startupreneur - Adam Faturahman; Nuke Puji Lestari Santoso; Prima Hafidz Mumtazi (LPPM Universitas Bhinneka Nusantara, 2026)
The post-pandemic digital economy growth opens significant opportunities for culinary startupreneurs in Indonesia; however, limited digital marketing budgets often lead to advertising budget waste. This study aims to analyze the potential utilization of Google Ads' Location Targeting feature as an efficient digital promotion strategy for a donut culinary startupreneur in Karawaci, Tangerang City. The research employs a descriptive quantitative method with a case study approach through the comparison of Google Ads dashboard metrics before and after location radius optimization (A/B Testing). The results indicate that implementing Location Targeting within a 7 km radius from the store location significantly reduced the Cost-Per-Acquisition (CPA) from IDR 37,500 to IDR 8,050 per order (a 78.53% reduction), while simultaneously increasing the Click-Through-Rate (CTR) from 1.5% to 6.8%. The sales conversion increase from 15 to 61 orders confirms that precise geographic targeting within a logistics-relevant radius effectively eliminates advertising budget waste. It can be concluded that Google Ads Location Targeting is an essential survival and escalation strategy for budget-constrained culinary startupreneurs, aligned with the business efficiency principles within the Sustainable Development Goals (SDG) 8 framework.